Anti-Aging Potential of Cosmos Caudatus Microgreens Extract Against Paraquat-Induced Oxidative Stress in Fruit Flies - Ramdani, Wandi; Takene, Giovanni; Aulia, Izdihara Arini; Dami, Theovilla Rika Rianty; Imanuel, Amos; Faimnasi, Maria Oktavian; Arlis, Nesya Zuba; Anggara, Vicky; Ginting Soeka, Alfredi Anis Fadhila; Palege, Ivan Jeremy Jethro; Sari, Intan Permata (International Journal of Aquatic Research and Environmental Studies, 2026)
Oxidative stress is a major contributor to aging and neurodegenerative diseases through excessive production of reactive oxygen species, leading to cellular damage and functional decline. Cosmos caudatus microgreens are rich in antioxidant compounds that may protect against oxidative stress-induced aging. This study investigated the anti-aging potential of Cosmos caudatus microgreens extract in a paraquat-induced oxidative stress model using Drosophila melanogaster. Male flies were assigned to four groups: control, paraquat at a concentration of 3.5 millimolar, 10 percent Cosmos caudatus microgreens extract, and 10 percent Cosmos caudatus microgreens extract combined with paraquat at a concentration of 3.5 millimolar. Antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl assay, while anti-aging effects were assessed through survival rate, locomotor performance, malondialdehyde concentration, and lipofuscin accumulation. The extract showed very strong antioxidant activity with an inhibitory concentration of 2.887 micrograms per milliliter and contained high chlorophyll and carotenoid levels. Paraquat exposure reduced survival and climbing ability while increasing malondialdehyde concentration and lipofuscin accumulation. Treatment with 10 percent Cosmos caudatus microgreens extract improved survival and locomotor performance and reduced malondialdehyde concentration and lipofuscin accumulation. The extract alone maintained normal physiological function and exhibited lower oxidative stress markers than the control group. These findings demonstrate that Cosmos caudatus microgreens possess strong antioxidant and anti-aging properties by reducing oxidative damage and preserving physiological function, highlighting their potential as a natural therapeutic candidate for preventing oxidative stress-related aging.
Keywords: Cosmos Caudatus, Microgreens, Antioxidant Activity, Anti-Aging, Malondialdehyde, Drosophila Melanogaster, Lipofuscin